Hypoxia Inducible Factor-1α (HIF-1α) and Some HIF-1 Target Genes are Elevated in Experimental Glaucoma - Ergorul, Ceren (2010)
Low levels of hypoxia have been suggested to be a mechanism of retinal damage in glaucoma. To test the hypothesis that the activation of the hypoxia-responsive transcription factor hypoxia inducible factor-1α (HIF-1α) is involved in the pathophysiology of glaucoma, we used a rat model of glaucoma to study (1) HIF-1α retinal protein levels by immunoblot analysis, (2) cellular localization of HIF-1α in the retina by immunohistochemistry, and (3) expression of retinal HIF-1 gene targets by quantitative real-time polymerase chain reaction. Glaucoma was unilaterally induced in rats by injecting hypertonic saline in episcleral veins. We find that HIF-1α protein was increased in the retina following elevation of intraocular pressure, specifically in Müller glia and astrocytes but not in activated microglia. Eight established HIF-1 target genes were measured in experimental glaucoma. Retinal Epo, Flt-1, Hsp-27, Pai-1, and Vegfa mRNA levels were increased and Et-1, Igf2, and Tgfβ3 levels were decreased in the glaucomatous retinas. Thus, the increase in HIF-1α levels in Müller glia and astrocytes is accompanied by a marked up regulation of some, but not all, HIF-1 transcriptional targets. These data support the hypothesis that HIF-1α becomes transcriptionally active in astrocytes and Müller cells but not microglia or neurons in glaucoma, arguing against a global hypoxia stimulus to the retina.